2022
DOI: 10.1186/s12888-022-04239-w
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of depressive symptoms among married Egyptian women: a multicenter primary healthcare study

Abstract: Background Depression affects about 3.8% of the world’s population. Although marriage may contribute to subjective well-being, some marital variables could increase women’s risk for depression. This study aimed to determine the prevalence of depressive symptoms and their correlates among married females attending primary healthcare facilities. Methods A cross-sectional study was conducted on a purposive sample of 371 married women at the primary he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Some factors were significantly associated with depression with a P value of less than 0.05 but were not significant predictors for depression, such as age group (18 -30 years), which was found to be significant in a study in Egypt [36]. Regarding gender, we found that it was significantly associated with depressive symptoms, with male participants having a higher prevalence than female participants (P-value = 0.03, AOR = 1.773 (1.056 -2976), likewise a study in Bangladesh [37].…”
Section: Discussionmentioning
confidence: 75%
“…Some factors were significantly associated with depression with a P value of less than 0.05 but were not significant predictors for depression, such as age group (18 -30 years), which was found to be significant in a study in Egypt [36]. Regarding gender, we found that it was significantly associated with depressive symptoms, with male participants having a higher prevalence than female participants (P-value = 0.03, AOR = 1.773 (1.056 -2976), likewise a study in Bangladesh [37].…”
Section: Discussionmentioning
confidence: 75%
“…Consistent with the present results, Lopez et al [5] and Upadhyaya et al in India [3] also found that that PP was more common in the 18-25 years age group. This is probably because pregnancy is more stressful for younger women who are usually not as psychologically prepared as the older ones for it [26,27] that mothers at the age of 35 years or older were at a higher risk of PP [28,29]. This finding, which is contrary to ours, may be attributed to the higher incidence of medical complications of pregnancy and delivery that is recorded among older mothers than among younger ones; for example, the higher rates of cesarean delivery and preterm birth that may be associated with a slightly increased risk of PP [30].…”
Section: Discussionmentioning
confidence: 99%
“…The married adults currently living together with their spouses in the households situated in Rajshahi City Corporation (RCC) area were considered as the study population. Since the number of households was known (99,222) [ 30 ], the required number of samples for the present study was calculated using the formula, [ 31 ], where n = the number of samples, z = 1.96, p = 0.302 (the prevalence of depression among married women was taken from a previous study [ 32 ], and d = 0.05 (margin of error). The formula provided that 324 households were the minimum required sample size for the study.…”
Section: Methodsmentioning
confidence: 99%